OP0300 A NEUTROPHIL SIGNATURE IS STRONGLY ASSOCIATED WITH CARDIOVASCULAR RISK IN GOUT. (June 2019) - Vedder, Daisy; Gerritsen, Martijn; Nurmohamed, Michael; Vollenhoven, Ronald van; Lood, Christian
Abstract : Background: Similar to other rheumatic diseases, patients with gout have an increased cardiovascular morbidity and mortality, not fully explained by traditional cardiovascular risk factors. Instead, gout-specific factors, including xanthine oxidase induced oxidative stress, increased lipid oxidization and chronic low-grade inflammation, have been suggested as important contributors.(1) Neutrophils, through formation of neutrophil extracellular traps (NETs), partake in pro-thrombotic and atherogenic processes contributing to cardiovascular disease.(2) However, the role of NETs in cardiovascular disease in human gout is not known. Objectives: Our objective is to investigate the association between neutrophil activation and cardiovascular risk in gout patients. We hypothesize that neutrophil activation mediates inflammation, as well as activation and damage to endothelial cells, partaking in atherosclerosis development. Methods: Plasma samples from 75 gout patients participating in the 'Reade gout cohort Amsterdam' were analyzed. Patient data was collected on disease activity, demographics, gout history, comorbidities, medication use and cardiovascular risk assessments. Measurements included anthropometry, vital parameters (RR, HF), ECG and lab variables. Levels of NETs, and NET-derived markers (cell-free DNA and peroxidase activity) were analyzed using a MPO-DNA ELISA, as well as fluorimetry. Levels of calprotectin (S100A8/A9) were analyzed by ELISA. Markers of NETosis were related to clinical markers of cardiovascular risk, including BMI, smoking, blood pressure, lipid profile and 10 year risk of cardiovascular mortality (SCORE EU). Results: No associations were found between markers of cell death (cfDNA and NETs) and cardiovascular risk. However, markers of neutrophil activation, including peroxidase activity correlated with BMI (r=0.31, p=0.008), waist-hip ratio (r=0.52, p<0.001), cholesterol ratio (r=0.51, p<0.001), and triglycerides (r=0.42, p<0.001). These associations were even stronger in patients with chronic, polyarticular gout. Peroxidase activity was associated with the 10 year risk of cardiovascular comorbidity (r=0.47, p<0.001, Figure 1A). Calprotectin levels were elevated in hypertension (p=0.005) and diabetes (p=0.02), with calprotectin levels associating with diabetes independently on BMI (OR=6.2, p=0.04). Finally, we constructed a neutrophil risk score ranging from 0-2 based on positivity for peroxidase and/or calprotectin to identify patients with a 'neutrophil activation signature'. The neutrophil risk score strongly associated with CVD risk (Figure 1B). Patients with neutrophil activation signature (risk score 1-2) had markedly elevated cardiovascular risk score (p=0.001), with 67.7% of the patients having high cardiovascular risk, versus 32.3% of the patients without a neutrophil activation signature (OR=2.9, p=0.03). Conclusion: We have demonstrated, for the first time, that neutrophil activation markers are associated with several risk factors of cardiovascular disease, including hyperlipidemia, hypertension and diabetes in a large cohort of gout patients. Furthermore, the presence of a neutrophil activation signature is strongly associated with a 10-year risk of cardiovascular comorbidity. References: [1] Krishnan E. Inflammation, oxidative stress and lipids: the risk triad for atherosclerosis in gout. Rheumatology (Oxford). 2010;49(7):1229-38. [2] Doring Y, et al. Neutrophil Extracellular Traps in Atherosclerosis and Atherothrombosis. Circ Res. 2017;120(4):736-43. Disclosure of Interests: Daisy Vedder Speakers bureau: Novartis, Martijn Gerritsen Grant/research support from: Grunenthal has sponsored the Reade Cohort, Michael Nurmohamed Grant/research support from: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Menarini, MSD, Mundipharma, Pfizer, Roche, Sanofi and UCB, Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Menarini, MSD, Mundipharma, Pfizer, Roche, Sanofi and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Menarini, MSD, Mundipharma, Pfizer, Roche, Sanofi and UCB, Ronald van Vollenhoven: None declared, Christian Lood: None declared